2013
DOI: 10.1152/japplphysiol.00225.2013
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine supplementation improves antioxidant defenses through l-arginine/nitric oxide pathways in exercised rats

Abstract: l-Arginine (l-Arg) supplementation has been shown to enhance physical exercise capacity and delay onset of fatigue. This work investigated the potential beneficial mechanism(s) of l-Arg supplementation by examining its effect on the cellular oxidative and nitrosative stress pathways in the exercised rats. Forty-eight rats were randomly divided into six groups: sedentary control; sedentary control with l-Arg treatment; endurance training (daily swimming training for 8 wk) control; endurance training with l-Arg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 41 publications
3
33
0
1
Order By: Relevance
“…Emerging evidence has revealed that arginine has antioxidant properties ( 30 , 31 ); thus, arginine supplementation exhibited a protective effect against radiation toxicity ( 32 34 ). Accordingly, we assumed that Ass1 might be a key molecule to determine the sensitivity toward genotoxic stress.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence has revealed that arginine has antioxidant properties ( 30 , 31 ); thus, arginine supplementation exhibited a protective effect against radiation toxicity ( 32 34 ). Accordingly, we assumed that Ass1 might be a key molecule to determine the sensitivity toward genotoxic stress.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of BCP with LA showed a comparable antioxidant effect with a standard group. The additive effect of BCP and LA combination treatment in oxidative stress might be because of increased expression of CB2 receptors and l ‐arginine/nitric oxide pathway (Shan, Wang, Gao, Cao, & Zhang, ). This shows a combinational approach of BCP and LA could reduce the oxidative stress in T2DM conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The differences that we observed for these two ratios between the HI-FIT and LO-FIT groups, as well as their weak correlations withV O 2 max , can be explained by at least three hypotheses. Second, changes in the expression and/or activity of cationic amino acid transporters responsible for the ADMA and L-arginine cellular influx and efflux could be altered with endurance exercise training (Shan, Wang, Gao, Cao, & Zhang, 2013) and contribute to differences in exchange dynamics of some of the L-arginine analogues between the two groups. Second, changes in the expression and/or activity of cationic amino acid transporters responsible for the ADMA and L-arginine cellular influx and efflux could be altered with endurance exercise training (Shan, Wang, Gao, Cao, & Zhang, 2013) and contribute to differences in exchange dynamics of some of the L-arginine analogues between the two groups.…”
Section: Discussionmentioning
confidence: 99%